2017
DOI: 10.1016/j.celrep.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of STAT3-Mediated Transcription during Early Human Th17 Cell Differentiation

Abstract: The development of therapeutic strategies to combat immune-associated diseases requires the molecular mechanisms of human Th17 cell differentiation to be fully identified and understood. To investigate transcriptional control of Th17 cell differentiation, we used primary human CD4 T cells in small interfering RNA (siRNA)-mediated gene silencing and chromatin immunoprecipitation followed by massive parallel sequencing (ChIP-seq) to identify both the early direct and indirect targets of STAT3. The integrated dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 43 publications
7
111
0
Order By: Relevance
“…49,50 STAT3 is a signaling molecule that regulates both T cell migration and Th17 differentiation. 51 These observations agree with our data showing that KCs initiate Th17 differentiation of naive T cells independent of the interaction between CD58 and CD2. Furthermore, the CD54/LFA-1-mediated phosphorylation of STAT3 fits our observation that STAT3 phosphorylation is still upregulated in naive T cells cultured with IFNγ-pretreated KCs in the absence of CD58/CD2-mediated costimulation.…”
Section: Discussionsupporting
confidence: 92%
“…49,50 STAT3 is a signaling molecule that regulates both T cell migration and Th17 differentiation. 51 These observations agree with our data showing that KCs initiate Th17 differentiation of naive T cells independent of the interaction between CD58 and CD2. Furthermore, the CD54/LFA-1-mediated phosphorylation of STAT3 fits our observation that STAT3 phosphorylation is still upregulated in naive T cells cultured with IFNγ-pretreated KCs in the absence of CD58/CD2-mediated costimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Both pY‐STAT3 levels and binding of STAT3 to the promoter region of PDK4 were highest in IL‐6‐stimulated Ctrl cells and reduced in the shSTAT3#456 and shSTAT3#843 cells compared to Ctrl (Appendix Fig S6C and D, Fig C). Known STAT3 targets Leucine Zipper ATF‐Like Transcription Factor (BATF) and JunB Proto‐Oncogene, AP‐1 Transcription Factor Subunit (JUNB) (Tripathi et al , ) were used as a positive control (Appendix Fig S6E and F, Table EV6). Immunoglobulin G (IgG) was used as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Primer sequences used for ChIP are listed in Table . Known STAT3 binding sites in BATF and JUNB promoters described in Tripathi et al () were chosen as positive controls and confirmed by extraction of corresponding peaks from ENCODE STAT3 ChIP‐Seq HeLa‐S3 data (ENCSR000EDC) with UCSC Genome Browser ( http://genome.ucsc.edu). For the generation of PDK4 primer pairs, a STAT3 binding site in the promoter region of PDK4 detected by ENCODE STAT3 ChIP‐Seq HeLa‐S3 was extracted (see Appendix Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…We explored the STAT3/STAT6 binding sites using transcription factor binding site prediction software JASPAR 37 as well as existing ChIP-seq data across different cell lines. [38][39][40] We validated multiple sites (Suppl . Table S7) for (A-C) Macrophages were treated for 1h with IL-4 and IL-6 alone or in combination for (A) STAT3 ChIP, (B) STAT6 ChIP and 6h for (C) H3K9ac ChIP for indicated genes (n ≥ 4-6).…”
Section: Analysis Of Human Macrophage Transcriptome Changes In Responmentioning
confidence: 99%